The impact of raw materials and baking conditions on Maillard reaction products, thiamine, folate, phytic acid and minerals in white bread. Issue 6 (14th March 2016) - Helou, Cynthia; Gadonna-Widehem, Pascale; Robert, Nathalie; Branlard, Gérard; Thebault, Jacques; Librere, Sarah; Jacquot, Sylvain; Mardon, Julie; Piquet-Pissaloux, Agnès; Chapron, Sophie; Chatillon, Antoine; Niquet-Léridon, Céline; et al.
Abstract : The aim of this study was to develop a white bread with improved nutrient contents and reduced levels of potentially harmful Maillard reaction products. Abstract : The aim of this study was to develop a white bread with improved nutrient contents and reduced levels of potentially harmful Maillard reaction products such as N ε -carboxymethyllysine (CML) and 5-hydroxymethylfurfural (HMF). Assays were carried out through a full factorial experimental design allowing the simultaneous analysis of four factors at two levels: (1) wheat flour extraction rates (ash content: 0.60%–0.72%), (2) leavening agents (bakers' yeast – bakers' yeast and sourdough), (3) prebaking and (4) baking conditions (different sets of time and temperature). The baking conditions affected HMF and CML as well as certain mineral contents. A reduced baking temperature along with a prolonged heat treatment was found to be favourable for reducing both the CML (up to 20%) and HMF concentrations (up to 96%). The presence of sourdough decreased the formation of CML (up to 28%), and increased the apparent amounts of calcium (up to 8%) and manganese (up to 17.5%) probably through acidification of the dough. The extraction rate of flours as well as interactions between multiple factors also affected certain mineral content. However, compounds like folate, thiamine, copper, zinc, iron and phytic acid were not affected by any of the factors studied.